2017
DOI: 10.3390/met7080309
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mechanical Property, and Phase Transformation of Quaternary NiTiFeNb and NiTiFeTa Shape Memory Alloys

Abstract: Ta 1 (at %) SMAs are fabricated. The microstructure, mechanical property, and phase transformation of NiTiFeNb and NiTiFeTa SMAs are further investigated. Ti 2 Ni and β-Nb phases can be observed in NiTiFeNb SMA, whereas Ti 2 Ni and Ni 3 Ti phases can be captured in NiTiFeTa SMA. As compared to NiTiFe SMA, quaternary NiTiFeNb and NiTiFeTa SMAs possess the higher strength, since solution strengthening plays a considerable role. NiTiFeNb and NiTiFeTa SMAs exhibit a one-step transformation from B2 austenite to B19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In early studies, the cold-rolled Ti 50 Ni 47.5 Fe 2.5 (at.%) alloy has two-way shape memory effect and low martensite transformation temperature [19]. Due to the excellent shape memory effect of Ti-rich Ti–Ni–Fe alloys, some researchers have developed the different Ti-rich Ti–Ni–Fe alloys [18,19,20,21,22,23,24,25,26,27,28]. The shape memory effect of Ti 50 Ni 47 Fe 2.5 Nd 0.5 alloy is improved when the trace amount of Nd is substituted for Ni [20], comparing with the Ti 50 Ni 47 Fe 2 Mo 1 and Ti 50 Ni 48 Fe 2 alloys [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In early studies, the cold-rolled Ti 50 Ni 47.5 Fe 2.5 (at.%) alloy has two-way shape memory effect and low martensite transformation temperature [19]. Due to the excellent shape memory effect of Ti-rich Ti–Ni–Fe alloys, some researchers have developed the different Ti-rich Ti–Ni–Fe alloys [18,19,20,21,22,23,24,25,26,27,28]. The shape memory effect of Ti 50 Ni 47 Fe 2.5 Nd 0.5 alloy is improved when the trace amount of Nd is substituted for Ni [20], comparing with the Ti 50 Ni 47 Fe 2 Mo 1 and Ti 50 Ni 48 Fe 2 alloys [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the microstructures of hot deformed Ti 50 Ni 47 Fe 3 alloy reported are strain localization, grain boundary serrations, and relatively fine near-equiaxed grains; at higher working temperature and higher strain rate, the content of dynamic recrystallization is higher; the increase of dynamically recrystallized grains results in the restraint of austenitic ↔ martensitic transformation [26,27]. Liang et al [28] reported that the Ti 51.8 Ni 45 Fe 3.2 alloy comprises a B2 austenite matrix and a Ti 2 Ni precipitate, and in the Ti 51.8 Ni 44 Fe 3.2 Nb 1 alloy with high yield strength, the Ti 2 Ni and β-Nb precipitates occur in the matrix of B2 austenite. In the Ti-rich Ti–Ni–Fe alloys, to obtain a large number of B2 TiNi phases, the heat-treated ingots were at high temperature for a long time, and the samples were cooled rapidly in ice water after heat treatment [18,19,20,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure of martensitic active shape memory alloys is dominated by equiaxed grains rather than dendrites, as noted in conventional nitinol alloys, making them less susceptible to corrosion. 28 Superelastic NiTi wires are unbreakable in vitro, 20 but they do break more frequently when used intraorally. In moderate-crowding cases, which require extended use of an aligning archwire, fracture of the initial wire is one of the most common problems.…”
Section: Et Almentioning
confidence: 99%
“…Liang et al studied NiTiFeNb and NiTiFeTa SMAs [26]. The microstructure, mechanical property, and phase transformation of NiTiFeNb and NiTiFeTa SMAs were investigated.…”
Section: Contributionsmentioning
confidence: 99%